PROSPECTS AND CHALLENGES FACED BY FOREIGN NATIONALS PURSUING HIGHER EDUCATION AT THE UNIVERSITY OF MYSORE, INDIA - Williams, Vasanthi Renna; Muhaiyya, Ramadhan (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Education is never restricted by boundaries. Knowledge is infinite and unbounded and needs to be shared. From time immemorial, people have been peripatetic and have been crossing borders in search of knowledge and enhancing their skill. Like many other countries, India too has been a preferred destination for education by many across the world. Of the several destinations for education in India, the University of Mysore, which is more than a decade old, has been a preferred choice for many. The University boasts of students not only from other States in India but from all over the world. This study tries to examine the rationale behind foreign students opting to study at the University of Mysore and the challenges they face with regard to education, imbibing knowledge and congenial atmosphere during their period of study.